Skin cancer of the head and neck with gross or microscopic perineural involvement: Patterns of failure. Issue 1 (July 2016) - Sapir, Eli; Tolpadi, Anagha; McHugh, Jonathan; Samuels, Stuart E.; Elalfy, Eman; Spector, Matthew; Shuman, Andrew G.; Malloy, Kelly M.; Prince, Mark E.; Bradford, Carol R.; Worden, Francis P.; Schipper, Matthew; et al.
Abstract: Objectives: Analyze patterns of failure of patients with head-and-neck cutaneous squamous cell carcinoma with perineural involvement: gross cranial nerve involvement (GCNI), microscopic focal perineural invasion (MFPNI), and microscopic extensive perineural invasion (MEPNI), managed with or without radiotherapy (RT). Materials and methods: Retrospective review: 102 patients with GCNI, MFPNI and MEPNI, observed or treated with RT from 2000 through 2013. The pathology specimens were reviewed for the purpose of the study. Results: 35 patients had GCNI, all irradiated definitely; 37% failed in-field, and two year disease free survival (DFS) rate was 56%. 19/30 patients (63%) with MEPNI without evidence of GCNI received adjuvant RT to the course of the nerves supplying the involved skin. Recurrence-free survival (RFS) in nerves (94% vs. 25%, P  = 0.01) and DFS (73% vs. 40%, P  = 0.05) were significantly higher in the irradiated MEPNI patients compared with the observed. 10/37 (27%) patients with MFPNI were irradiated adjuvantly. MFPNI had low rate of neural and overall failure, without significant benefit to irradiation over observation. Conclusions: In patients with GCNI radiotherapy achieves a substantial chance of disease control. Radiotherapy to nerves at risk in MFPNI did not affect outcome, but in MEPNI it achieved less gross perineural recurrences and better DFS, compared with observation.